Dietary Fiber Extraction from Defatted Corn Hull by Hot-Compressed Water - Wang Li; Liu Hua-Min; Xie Ai-Jun; Zhu Chun-Yan; Qin Guang-Yong (Polish Journal of Food and Nutrition Sciences)
Corn hulls were abundant and inexpensive byproducts of the corn dry or wet milling processes, but most of them were discarded as agro-wastes. The aim of this study was to extract the dietary fiber by hot-compressed water (HCW) from defatted corn hull and to determine the chemical properties. Results showed that temperature and time played critical roles in extraction efficiency; the maximal yield of dietary fiber A (DFA) extracted by HCW reached 33.0% at 150°C for 60 min. The yield of dietary fiber B (DFB) increased from 2.0% to 56.9% as the temperature increased from 110 to 180°C, while the yield of solid residue (SR) decreased from 88.7% to 27.7%. Fourier transform infrared spectroscopy (FT-IR) results demonstrated that C-H, O-H, C=O, COO- occurred in the DFA, SR and DFB. The dietary fiber polysaccharides consisted of arabinose, galactose, glucose, xylose and uronic acid.